1988
DOI: 10.1111/j.1432-1033.1988.tb13801.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of cathepsin B from rabbit skeletal muscle

Abstract: Cathepsin B was purified from rabbit skeletal muscle by ammonium sulfate fractionation and successive chromatographies on Sephadex G-75, phosphocellulose, peptide-conjugated Sepharose, DEAE-Toyopearl and Sephadex G-100. The purified enzyme gave a single protein band on SDS/polyacrylamide gel electrophoresis. The enzyme did not abolish the Ca sensitivity of the ATPase activity of myofibrils. The molecular mass of the enzyme was found to be 27 kDa on gel filtration and SDS/polyacrylamide gel electrophoresis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 14 publications
2
39
0
Order By: Relevance
“…Mechanism of the increase in peptides In the muscle, there are lysosomal cathepsins B (Okitani et al, 1988), D (Suzuki & Fujimaki, 1968;Fukushima et al, 1971) (Okitani et al, 1985) and L (Okitani et al, 1980b) which are most active in an acidic pH region, sarcoplasmic p-and m-calpains (Dayton et al, 1976(Dayton et al, , 1981Ishiura et al, 1978), which are activated by Ca2+ and exhibit most activities in a neutral pH region, and a proteasome (Dahlmann et al, 1985;Driscoll & Goldberg, 1989;Matsuishi & Okitani, 1997) dependent on ATP for activation. It is reported that cathepsins B, D and L degrade myofibrillar proteins, while cathepsin H scarcely causes hydrolysis ofthese proteins (Okitani et al, 1980b;Ouali et al, 1987).…”
Section: Improvement Of Meat Tastementioning
confidence: 99%
See 1 more Smart Citation
“…Mechanism of the increase in peptides In the muscle, there are lysosomal cathepsins B (Okitani et al, 1988), D (Suzuki & Fujimaki, 1968;Fukushima et al, 1971) (Okitani et al, 1985) and L (Okitani et al, 1980b) which are most active in an acidic pH region, sarcoplasmic p-and m-calpains (Dayton et al, 1976(Dayton et al, , 1981Ishiura et al, 1978), which are activated by Ca2+ and exhibit most activities in a neutral pH region, and a proteasome (Dahlmann et al, 1985;Driscoll & Goldberg, 1989;Matsuishi & Okitani, 1997) dependent on ATP for activation. It is reported that cathepsins B, D and L degrade myofibrillar proteins, while cathepsin H scarcely causes hydrolysis ofthese proteins (Okitani et al, 1980b;Ouali et al, 1987).…”
Section: Improvement Of Meat Tastementioning
confidence: 99%
“…It is reported that cathepsins B, D and L degrade myofibrillar proteins, while cathepsin H scarcely causes hydrolysis ofthese proteins (Okitani et al, 1980b;Ouali et al, 1987). Zeece et al (1986) and Lisa et al ( 1995) reported that calpain is involved in the degradation of myofibrillar proteins during the postmortem storage of meat.…”
Section: Improvement Of Meat Tastementioning
confidence: 99%
“…The main changes in myofibrillar are reported to occur in myosin light-chain but actin and actinin also degrade during storage period (Careche et al, 1998;Kjaersgard et al, 2006;Schubring, 2005). Numerous studies attributed the degradation of myofibrillar to proteases such as cathepsins, as well as calcium-dependent proteases (Okitani et al, 1980;Zhang et al, 2015). In several marine species, cathepsins B, D, and L were considered as the enzymes playing the most important role in postmortem muscle softening (Ladrat et al, 2003).…”
Section: Myofibrillar Protein Analysesmentioning
confidence: 99%
“…Of the proteases involved in postmortem aging, calpains, 9) cathepsins, 10,11) and aminopeptidases 12,13) have been purified, but the purification of proteases requires considerable effort and cost. Furthermore, because postmortem aging of meat is caused by the combined effects of proteases, it is not practical to determine the degree of postmortem aging using only one isolated protease.…”
mentioning
confidence: 99%